2018
DOI: 10.1371/journal.pone.0207397
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, local viscoelasticity and cell culture suitability of 3D hybrid HA/collagen scaffolds

Abstract: As mechanical properties of cell culture substrates matter, methods for mechanical characterization of scaffolds on a relevant length scale are required. We used multiple particle tracking microrheology to close the gap between elasticity determined from bulk measurements and elastic properties sensed by cells. Structure and elasticity of macroporous, three-dimensional cryogel scaffolds from mixtures of hyaluronic acid (HA) and collagen (Coll) were characterized. Both one-component gels formed homogeneous netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 57 publications
0
30
0
1
Order By: Relevance
“…It is only for chemically crosslinked Coll networks that such a comparison exists. 41 In that latter study, local elastic moduli of Coll cryogels determined from MPT measurements were much lower than the corresponding bulk shear moduli. Analogous to earlier investigations on intermediate filament networks, 42 this was attributed to a pronounced contribution of stretched, out of equilibrium chain segments between network junctions or to densely crosslinked areas not accessible to the tracer particles, thus not contributing to the MPT modulus, but showing up in the bulk modulus.…”
Section: Introductionmentioning
confidence: 80%
“…It is only for chemically crosslinked Coll networks that such a comparison exists. 41 In that latter study, local elastic moduli of Coll cryogels determined from MPT measurements were much lower than the corresponding bulk shear moduli. Analogous to earlier investigations on intermediate filament networks, 42 this was attributed to a pronounced contribution of stretched, out of equilibrium chain segments between network junctions or to densely crosslinked areas not accessible to the tracer particles, thus not contributing to the MPT modulus, but showing up in the bulk modulus.…”
Section: Introductionmentioning
confidence: 80%
“…Nonetheless, Wernike et al [ 170 ] demonstrated that cyclic loadings can help chondrocytes seeded into a polyurethane scaffold to maintain their phenotype as assessed by type II collagen measurement for short term culture, despite the fact that hypoxia seemed to be more efficient to prevent chondrocyte de-differentiation. While many studies were focused on the macroscopic level of Young’s modulus (i.e., of the whole material), cells interact only with their surroundings whose local Young’s modulus value can sometimes be smaller than the one of the bulk material [ 171 ]. Nonetheless, Grier et al [ 172 ] showed that tenocytes are sensitive to the way that collagen-GAG scaffold resisted to contractile forces of cells.…”
Section: Review Of the Influence Of The Scaffold Architecture On Cmentioning
confidence: 99%
“…This finding is in accordance to Roether et al, who described significantly lower local elasticities of proteinaceous, cryogelated scaffolds in comparison to the bulk modulus. [64] Figure 2. Generation of biocompatible high-precision 3D printed cell scaffolds.…”
Section: Mechanical Characterization Of Biological Microscaffolds Witmentioning
confidence: 99%
“…Observing deviations of protein-based scaffold mechanics over time can reveal information about the aging of cross-linked hydrogels and can, therefore, indicate degradation processes or swelling. [64] This is especially important to consider when conducting cell experiments over several days or weeks. BSA-RB scaffolds stored in cell culture conditions were stable, while a softening was observed when stored in PBS at 4°C (Figure 4A).…”
Section: Mechanical Characterization Of Biological Microscaffolds Witmentioning
confidence: 99%